2004
DOI: 10.1097/01.mlg.0000147933.14014.12
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Nasal Polyposis and Endonasal Endoscopic Surgery: Long‐Term Results, a 65‐Case Study

Abstract: Endoscopic sphenoethmoidectomy is indicated for nasal polyposis refractory to intensive medical management with a good improvement of patient's quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 26 publications
1
18
0
3
Order By: Relevance
“…Most authors agree on the fact that management of NP should be based primarily on a strictly medical approach, to be completed by surgery only in the case of corticosteroid failure [9,11,12]. The results of the present study show that combined surgery and corticosteroid therapy is effective in the treatment of severe NP, producing significant and long-term improvements in symptoms and in the size of nasal polyps [8,13]. A significant improvement in symptoms (p B/0.001) occurred during the first months after surgery.…”
Section: Discussionsupporting
confidence: 59%
“…Most authors agree on the fact that management of NP should be based primarily on a strictly medical approach, to be completed by surgery only in the case of corticosteroid failure [9,11,12]. The results of the present study show that combined surgery and corticosteroid therapy is effective in the treatment of severe NP, producing significant and long-term improvements in symptoms and in the size of nasal polyps [8,13]. A significant improvement in symptoms (p B/0.001) occurred during the first months after surgery.…”
Section: Discussionsupporting
confidence: 59%
“…Facial pain decreased in reverse order (Table 1) also re ecting EPOS 2012 guidelines (26) where the importance of facial pain as who detected no signi cant di erences in the VAS score for nasal congestion, nasal discharge and smell impairment among CRSwNP, CRSwNP-A, and CRSwNP-AA patients (33,34) . In contrast to our data, Alobid et al could not nd signi cant di erences between aspirin-tolerant and intolerant NP patients with asthma, in terms of nasal polyp size (35) .…”
Section: Discussionmentioning
confidence: 52%
“…In this study a maximum score was seen for nasal obstruction in both group 1 (6.80) and group 2 (6.77), followed by nasal discharge, sneezing, facial pain of 3.87, 3.17 and 4.20 respectively Similar results have been reported by Dufour X et al, Poetkar DM et al also reported similar results. 34,35 Magdy et al and Kakkar V et al, also reported results in a similar manner with a little difference in their scores. 7,9 Postoperative visual analog scale and diagnostic nasal endoscopy scores…”
Section: Preoperative Visual Analog Scale Scores and Diagnostic Nasalmentioning
confidence: 54%